Targeting NOX enzymes in the central nervous system: therapeutic opportunities - Sorce, Silvia; Krause, Karl-Heinz; Jaquet, Vincent (Cellular and molecular life sciences : CMLS, 2012)
Among the pathogenic mechanisms underlying central nervous system (CNS) diseases, oxidative stress is almost invariably described. For this reason, numerous attempts have been made to decrease reactive oxygen species (ROS) with the administration of antioxidants as potential therapies for CNS disorders. However, such treatments have always failed in clinical trials. Targeting specific sources of reactive oxygen species in the CNS (e.g. NOX enzymes) represents an alternative promising option. Indeed, NOX enzymes are major generators of ROS, which regulate progression of CNS disorders as diverse as amyotrophic lateral sclerosis, schizophrenia, Alzheimer disease, Parkinson disease, and stroke. On the other hand, in autoimmune demyelinating diseases, ROS generated by NOX enzymes are protective, presumably by dampening the specific immune response. In this review, we discuss the possibility of developing therapeutics targeting NADPH oxidase (NOX) enzymes for the treatment of different CNS pathologies. Specific compounds able to modulate the activation of NOX enzymes, and the consequent production of ROS, could fill the need for disease-modifying drugs for many incurable CNS pathologies.